2021
DOI: 10.1002/acm2.13427
|View full text |Cite
|
Sign up to set email alerts
|

Fast generation of lung SBRT plans with a knowledge‐based planning model on ring‐mounted Halcyon Linac

Abstract: Purpose To demonstrate fast treatment planning feasibility of stereotactic body radiation therapy (SBRT) for centrally located lung tumors on Halcyon Linac via a previously validated knowledge‐based planning (KBP) model to support offline adaptive radiotherapy. Materials/methods Twenty previously treated non‐coplanar volumetric‐modulated arc therapy (VMAT) lung SBRT plans (c‐Truebeam) on SBRT‐dedicated C‐arm Truebeam Linac were selected. Patients received 50 Gy in five fractions. c‐Truebeam plans were re‐optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Wada et al [35] used a simplified knowledge-based planning model to design the Halcyon VMAT-SBRT plans for lung cancer, and the plan quality was clinically acceptable. In order to validate the feasibility of Halcyon-based rapid SBRT plans for central lung cancer, Visak et al [36] designed lung cancer SBRT plans using the KBP model, and new plans similar or better in dosimetry to the TB plans were obtained within 30 min, where the CI difference was not significant ( P > .05). Halcyon SBRT plans had a mean lower GI of 0.43 ( P = .006), an increase in maximum target dose of 2.9 Gy ( P < .001), and a mean reduction in lung mean lung dose of 0.10 Gy ( P = .004).…”
Section: Resultsmentioning
confidence: 99%
“…Wada et al [35] used a simplified knowledge-based planning model to design the Halcyon VMAT-SBRT plans for lung cancer, and the plan quality was clinically acceptable. In order to validate the feasibility of Halcyon-based rapid SBRT plans for central lung cancer, Visak et al [36] designed lung cancer SBRT plans using the KBP model, and new plans similar or better in dosimetry to the TB plans were obtained within 30 min, where the CI difference was not significant ( P > .05). Halcyon SBRT plans had a mean lower GI of 0.43 ( P = .006), an increase in maximum target dose of 2.9 Gy ( P < .001), and a mean reduction in lung mean lung dose of 0.10 Gy ( P = .004).…”
Section: Resultsmentioning
confidence: 99%
“…Several research groups have compared the performance of the Halcyon linear accelerator to that of the TrueBeam and Novalis Tx linear accelerators for various sites and techniques such as CSI, head neck, liver SBRT, spine SBRT, prostate SBRT, and pelvic node SBRT 14 , 23 28 . In terms of target coverage, dose conformity, and OAR dose constraints, all authors reported acceptable Halcyon dosimetric plans.…”
Section: Discussionmentioning
confidence: 99%